Assessing Cephalopods Fisheries in the Strait of Sicily by Using Poor Data Modeling - Geraci, Michele L.; Falsone, Fabio; Gancitano, Vita; Scannella, Danilo; Fiorentino, Fabio; Vitale, Sergio (Frontiers in Marine Science, 2021)
Cephalopods, including octopuses, squids, and cuttlefishes, are exploited by both bottom trawl and small-scale fisheries (SSF) in most of the Mediterranean areas. Bottom trawl fisheries regard cephalopods as a valuable bycatch, whereas for SSF, they are among the main target species. Cephalopods account for a relatively small proportion of the total landings in the Mediterranean. However, from an economic point of view, four cephalopods, Eledone cirrhosa, Eledone moschata, Octopus vulgaris, and Sepia officinalis, account for approximately 15% of the total landing value. Despite their economic importance, there are very few stock assessments of cephalopods in the Mediterranean because it is difficult to assess them by classical age-based methods, given their short life-cycles, and highly variable growth and recruitment. The production of E. cirrhosa, E. moschata, Illex coindettii, Loligo vulgaris, O. vulgaris, S. officinalis, and Todaropsis eblanae in the waters off the south of Sicily accounts for approximately 8% of the total Mediterranean yield of cephalopods. This study presents the first attempt to assess the state of these cephalopods in the Strait of Sicily by using surplus production models. Since species-wise landing statistics may be unreliable because of their morphological similarity, some octopuses (E. cirrhosa and E. moschata) and ommastrephid squids (I. coindetii and T. eblanae) were assessed combined. Landing data and abundance indices from trawl surveys were used to describe cephalopod stock dynamics through the Bayesian State Space Schaefer model (BSM) and Surplus Production model in Continuous Time (SPiCT) models. As survey data were not considered reliable indicators of their abundance, O. vulgaris, S. officinalis, and L. vulgaris stocks were assessed using the Catch-Maximum Sustainable Yield (CMSY) model. Overall, squid and cuttlefish stocks were observed to be in healthy conditions. However, assessments of octopus stocks indicated that their condition was critical or recovering. Here, we discuss the different stock statuses in the light of evolving fisheries and environmental factors in the area over time. Although cephalopods are not a priority in the current management system of Mediterranean fisheries, the importance of these species in the food web and their relevance for SSF underline their importance and their exploitation status should be periodically evaluated.